2005
DOI: 10.1073/pnas.0503402102
|View full text |Cite
|
Sign up to set email alerts
|

TrwB, the coupling protein involved in DNA transport during bacterial conjugation, is a DNA-dependent ATPase

Abstract: Bacterial conjugation is an example of macromolecular trafficking between cells, based on the translocation of single-stranded DNA across membranes through a type IV secretion system. TrwB⌬N70 is the soluble domain of TrwB, an essential integral membrane protein that couples the relaxosome (a nucleoprotein complex) to the DNA transport apparatus in plasmid R388 conjugation. TrwB⌬N70 crystallographic structure revealed a hexamer with six equivalent subunits and a central channel. In this work, we characterize a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
126
1
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(135 citation statements)
references
References 26 publications
2
126
1
6
Order By: Relevance
“…identified as a DNA-dependent ATPase (Tato et al, 2005). The discovery that a coupling protein is able to hydrolyse ATP substantiates the finding that key, well-conserved residues in the Walker A and B regions are necessary for conjugative transfer.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…identified as a DNA-dependent ATPase (Tato et al, 2005). The discovery that a coupling protein is able to hydrolyse ATP substantiates the finding that key, well-conserved residues in the Walker A and B regions are necessary for conjugative transfer.…”
Section: Discussionmentioning
confidence: 50%
“…The SpoIIIE protein has DNA-dependent ATP hydrolysis activity that is used to pump DNA during sporulation (Bath et al, 2000). The R388 coupling protein also has DNA-dependent ATP hydrolysis activity, and the Walker motifs of R388, RP4 and F plasmid have been demonstrated to be involved in conjugation (Moncalian et al, 1999;Schroder et al, 2002;Tato et al, 2005). Mutational analyses of the Walker A and B motifs of the RP4 coupling protein, TraG, revealed that only two mutations completely abolished RP4 transfer: K187T in Walker A, and D449N in Walker B (Balzer et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extrusion thus is unlikely to occur unless the neighboring protomer binds the second ligand, and we are led to anticipate a positive cooperative kinetics in transport. Positive cooperativity was indeed reported for ATP hydrolysis in the dimeric MalK in the maltose transporter complex (24) and in the hexameric ATPase TrwB involved in DNA transfer in conjugation (25), although kinetic analysis has been difficult with the classical F 1 ATPase (26,27). Although it was disappointing to find no evidence for positive cooperativity for nitrocefin, there was ample evidence for that for cephalothin, cefamandole, and cephaloridine.…”
Section: Discussionmentioning
confidence: 80%
“…In both cases, the template was TrwB, an hexameric integral membrane protein encoded by the conjugative plasmid R388 that is involved in the movement of the relaxosome DNA-binding complex toward the T4SS (28). TrwB belongs to the RecA protein-like family (26) and it displays a DNA-dependent ATPase activity (10,29,30). Likewise, TrwK, also encoded by plasmid R388, is also able to hydrolyze ATP (8).…”
Section: Structural Comparison Between Trwb and Trwk Proteins-mentioning
confidence: 99%